Pembelajaran Inovatif untuk Menanamkan Nilai-Nilai Karakter pada Siswa Sekolah Dasar Negeri Sukaluyu Kabupaten Bandung - Reni, Reni; In in Indriani, In in Indriani; Mohamad Rahmatuloh, Mohamad Rahmatuloh; Agung Ramadhan, Agung Ramadhan; Yosal Iriantara, Yosal Iriantara (PT. Solusi Komunikasi Terapan, 2024)
The problem of decreasing children’s morals occurs in school-age children. One effort to solve the problem of declining morals in school-aged children is to apply character education to elementary school students. Character education methods that have a real impact can generally only be obtained in full and in detail through reading the results of research and/or development. Several character education methods are the subject of study. The focus of this research is to identify innovative learning strategies and media that can be used to instill character values in students. The method used is document study. Initially the researcher will collect as many sources as documents as possible as a comparison for data accuracy. The discussion was carried out on two things (1) strategies and the role of innovative learning media to instill character values in Sukaluyu State Elementary School students, Bandung Regency (2) analysis of the novelty of the substance of character education methods which became material for study or development in 2011-2013 and (3) the form of character education in innovative learning methods which are the material for study or development. As a result, several alternative learning strategies that can be used to integrate character education are: PPR, role playing, TGT, ARCS, and simulation. Meanwhile, alternative learning media that can be used are: story media, flash media, comic media, and ring media.